Conformational, vibrational spectroscopic, nonlinear optical activity, and structure–activity studies on 2-hydroxy-3, 5-dinitropyridine: Combined experimental and density functional theory approach. Issue 3 (15th March 2016) - Asath, R. Mohamed; Rekha, T. N.; Rajkumar, Beulah J. M.; Premkumar, S.; Jawahar, A.; Mathavan, T.; Franklin Benial, A. Milton
ABSTRACT: The conformational analysis was carried out to predict the most stable, optimized structure of 2-hydroxy-3, 5-dinitropyridine among various conformers. The most stable, optimized structure of the molecule was predicted by the density functional theory (DFT) using the B3LYP method with the cc-pVQZ basis set. The vibrational frequencies, natural atomic charge distribution, and thermodynamic properties were calculated. The molecular electrostatic potential surface and contour map were simulated. The experimental and theoretical vibrational frequencies were assigned on the basis of potential energy distribution calculation. The density of states (DOS) spectrum was simulated. The frontier molecular orbital analysis was carried out. The natural bond orbital (NBO) analysis was performed to evaluate the donor–acceptor interactions in the molecule. The structure–activity descriptors were determined by Fukui functions and local reactivity descriptor calculations. The nonlinear optical (NLO) activity of the molecule was studied. The second harmonic generation test confirms the NLO activity of the title molecule.